Evaluation of real-time PCR with serology for diagnosis of community acquired pneumonia caused by Mycoplasma pneumoniae - Anand Manoharan; M.S. Ramya; Sara Chandy; P.N. Ranjitha; Abdul Hameed; Gothai S. Nachiyar; S. Balasubramanian (Elsevier, 2022)
Objective: To evaluate the utility of real-time polymerase chain reaction (PCR) against serology (IgM) for the diagnosis of community acquired pneumonia (CAP) caused by Mycoplasma pneumoniae (M. pneumoniae). Methods: Hospitalized children from 1 month to 18 years of age with symptoms and findings consistent with CAP as per World Health Organization (WHO) criteria were enrolled. Mycoplasma IgM serology (Acute phase) was done in all children using enzyme-linked immunosorbent assay (ELISA). Real-time PCR was done using a commercial FDA approved Multiplex Real-time PCR kit for M. pneumoniae. Results: M. pneumoniae was confirmed in 15% (10 out of 66 patients) of the hospitalized children with CAP. Of those with confirmed Mycoplasma infection, 90% (9 out of 10) patients were serology reactive while PCR was positive in only 40% (4 out of 10). Both IgM and PCR were positive in 30% (3 out of 10 patients) and only one real-time PCR positive patient was negative for IgM. Conclusion: In our study, real-time PCR had a lower sensitivity compared to serology. However, this test has the advantage of detecting early infection prior to the development of an immune response (presence of IgM). Clinicians could consider real-time PCR testing if the patient presents early after onset of symptoms and prior to the use of empirical antibiotics and serology should be the test of choice at late presentations.